Implementasi Pengembangan Tenaga Pendidik Guru BK: Studi Kasus di SMP Negeri 2 Sukodono - Rochmah, Jazilatur; Safitri, Nadia Eka Dewi; Trihantoyo, Syunu (Lembaga Yasin AlSys, 2024)
The arrangement on the advancement of counseling instructors is an imperative perspective of making strides the quality of direction and counseling administrations in present day instructive settings. This brief examines the challenges and prospects of implementing such a policy in the current educational environment. Challenges include limited resources, gaps in access to training and resistance to change. Be that as it may, with the proper approach, there's extraordinary potential to move forward the quality of instructive administrations, back all encompassing understudy improvement and create a positive learning environment. Recommendations include updating curricula, improving accessibility to training, emphasizing practical skills, strong organizational support, building professional networks and continuous evaluation. By actualizing these proposals, it is anticipated that the usage of the counseling instructor teacher improvement arrangement will have a positive affect on the quality of instruction and the welfare understudies.